Studi Problematika Pelaksanaan Pengajaran Bahasa Arab Dan Usaha Pemecahannya Di Madrasah Tsanawiyah Muhammadiyah 03 Sedayulawas Brondong Lamongan - Bahrus Surus, Lia Atiyah Rohmah (Jurnal Mahasiswa Pendidikan, 2021)
This thesis aims to find out what problems are faced in teaching Arabic at Madrasah Tsanawiyah Muhammadiyah 03 Sedayulawas Brondong Lamongan, as well as to find out the efforts made in overcoming these problematics. The results obtained from this study are that there are probles in the implementation of teaching Arabic, naely: The Problem of students is that when receiving teaching 58% "a lot" are difficult to understand. From the factor of educators (teachers) only 2% means "less" is a problem. From the objective factor, it is also less of a problem in the implementation of teaching Arabic because only 11% stated that they did not clearly understand the purpose of learning Arabic. Problems with educational tools, one of which is the method used by teachers in teaching Arabic, is "enough" (25.5%) to be a problem. In addition, the teaching aids used by the teacher are "a lot" (54.5%) which is a problem in teaching Arabic. Meanwhile, environmental factors (family) can be said to be "enough" to be a problem (40%) in teaching Arabic because they are very lacking in paying attention to/motivating their children to learn Arabic lessons. The efforts made in overcoming these problems are the first, the efforts of the students, namely by reading Arabic books, and taking additional lessons outside of school hours. Second, the efforts of the Arabic language teacher, namely by increasing the hours of Arabic lessons outside of school hours, the teacher is trying to find the right method to be taught, while those related to teaching aids are the absence of complete teaching aids (still in the stage of being worked on), teachers try to maximize the use of existing media and increase teacher creativity, which is related to evaluation, teachers try to continuously conduct evaluations. Third, the efforts of the school, namely seeking the equipment needed gradually for the further development of Arabic language teaching, as well as holding meetings with the parents of students and providing understanding to the guardians of students to motivate and support their children in learning Arabic.